Sigiriya : Kassapa's homage to beauty - Gunasiṃha, Siri. (Colombo : Vijitha Yapa Publications, 2008)
On Sigiriya garden and fortifications of Sri Lanka.
Includes some couplets in Sinhalese with translations to English.
Keywords: Mural painting and decoration -- Sri Lanka -- Sigiriya; Sigiriya (Sri Lanka)